Digitized information management: The dynamic information system - Halonen, R. (Journal of Digital Information Management, 2007)
This research focuses on the change process that led to a digitized information system in academia. The development was carried out in a project where the participants represented their universities. The biggest issue to manage was to define the electronic process that was to be coded to support student mobility between universities. Action research was chosen as the research method because of the strong involvement of the researcher in the case. The output was evaluated satisfied, even excellent by the users and the goal was achieved despite minor knowledge about designing information systems in the project group.
Keywords: Change process; Digitizing; Interorganizational information system; User participation